(untitled) (Czech Journal of International Relations, 1967)
"Munich" became a term of modern history due to the decision of the three great powers, by which Czechoslovakia was released from Nazi aggression on the eve of the Second World War. Unfortunately, it did not remain only a historical term acts and talks about this question, which should long ago have been only the subject of a historian’s study. In 1938, the people of the world could have really thought that the Munich Agreement would avert the danger of wolves and ensure peace in Europe. Due to its anti-Soviet and anti-progressive focus, the concession policy, which manifested itself, among other things, in the policy of non-intervention in the civil war in Spain, was essentially a support for the fascist rebels and could not stop the aggressors. "Munich" became only a prelude to the Second World War, which then broke out in just a year. The unnecessaryness of the Munich conference was evident even earlier. The occupation of the Czech lands and the creation of the Slovak state in mid-March 1939 showed Nazi Germany has clearly not retreated from its ambitious plans and intends to carry them out regardless of the rest of the country. Even against their own promises, which his partners still believed in at that time.